Analisis Pergerakan Harga Saham pada Jakarta Islamic Index Tahun 2019-2023 Secara Fundamental - Fahrini, Anisa Dwi; Legowati, Diah Ayu; Fitriyanto, Arief (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the influence of fundamental analysis on stock prices in the JII for the 2019-20223 period. The data used is secondary data from annual financial reports. The sample in this study is 14 companies listed on the JII during the period 2019-2023, selected using purposive sampling technique. The data analysis used is panel data regression analysis with Eviews 12 application. The results of this study indicate that the Return on Equity (ROE) does not have a significant effect on stock prices partially, Debt to Equity Ratio (DER) has a significant negative effect on stock prices, and Current Ratio (CR) has a significant positive effect on stock prices. It is also explained that the R-Squared value is 0.9459 meaning that ROE, DER, and CR have a very strong correlation in influencing stock prices, accounting for 94.59%.